In Search for the Retrievable Memory Trace in an Insect Brain - Menzel, Randolf (Frontiers in Systems Neuroscience, 2022)
The search strategy for the memory trace and its semantics is exemplified for the case of olfactory learning in the honeybee brain. The logic of associative learning is used to guide the experimental approach into the brain by identifying the anatomical and functional convergence sites of the CS and US pathways. Two of the several convergence sites are examined in detail, the antennal lobe as the first order sensory coding area, and the input region of the mushroom body as a higher order integration center. The memory trace is identified as the pattern of associative change on the level of synapses. Synapses are recruited, drop out and change their transmission properties for both the specifically associated stimulus and the not associated stimulus. Several rules extracted from behavioral studies are found to be mirrored in the patterns of synaptic change. The question is discussed whether an external reading of the content of the memory trace may ever be possible, and doubts are raised on the basis that the retrieval circuits are part of the memory trace.